POLITICAL TRANSFORMATIONAL LEADERSHIP IN LOCAL GOVERNMENT: AN ANALYSIS OF THE LEADERSHIP OF KARO REGENT ANTONIUS GINTING AND ITS IMPLICATIONS FOR LOCAL BUREAUCRACY AND GOVERNANCE - Lorentina Br. Sembiring; Bengkel; Indra Fauzan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research is motivated by the importance of political leadership in encouraging changes in local governance through a transformational leadership approach applied by the Regent of Karo, Antonius Ginting. The research aims to analyze the implementation of transformational leadership, its role in realizing the principles of good governance, and its implications for the effectiveness of the bureaucracy and the community of Karo Regency. The method used is qualitative research with an exploratory approach through interviews, observations, and documentation. The results of the study show that Antonius Ginting applies the characteristics of transformational leadership through a change in the bureaucratic work culture that is more disciplined, responsive, and oriented to public services. Its implementation can be seen in strengthening the supervision of apparatus performance, increasing coordination between regional apparatus organizations, and developing governance innovations. The leadership also encourages the application of the principles of transparency, accountability, and participation in local government. The implications can be seen in increasing bureaucratic effectiveness, the quality of public services, and the government's responsiveness to the needs of the community. These findings confirm that transformational leadership plays an important role in bureaucratic reform and strengthening more professional and adaptive local governance.